A Density Functional Investigation of the Reaction Mechanism of CH3OH + HS• - Nguyen, Trong Nghia; Nguyen, Hong Duong; Nguyen, Ngoc Tue; Nguyen, Thi Minh Hue (Old Journal, 2019)
CH3OH is one of potential alternative fuels. Potential energy surface of the CH3OH + HS• reaction has been revealed at the CCSD(T)/B3LYP/aug-cc-pVTZ level of theory. The chemical quantum results show that the reaction mainly occurs when the HS radical abstracts the H atoms in the OH and CH3 group of the CH3OH molecule via energy barriers at 18.2 and 9.0 kcal/mol, respectively. The predicted heats of reaction at 0 K of the corresponding products, 14.5 va 5.2 kcal/mol, are close to the experimental values, 14.5 va 5.2 kcal/mol, respectively. Similarly, the predicted heats of reaction at 298 K and the predicted geometry parameters for the reactants and products in this work are in good agreement with the available experimental data.